PI3K is critical for the nuclear translocation of IRF-7 and type I IFN production by human plasmacytoid predendritic cells in response to TLR activation - Guiducci, Cristiana (The Rockefeller University Press, 2008)
Plasmacytoid predendritic cells (pDCs) are the main producers of type I interferon (IFN) in response to Toll-like receptor (TLR) stimulation. Phosphatidylinositol-3 kinase (PI3K) has been shown to be activated by TLR triggering in multiple cell types; however, its role in pDC function is not known. We show that PI3K is activated by TLR stimulation in primary human pDCs and demonstrate, using specific inhibitors, that PI3K is required for type I IFN production by pDCs, both at the transcriptional and protein levels. Importantly, PI3K was not involved in other proinflammatory responses of pDCs, including tumor necrosis factor α and interleukin 6 production and DC differentiation. pDCs preferentially expressed the PI3K δ subunit, which was specifically involved in the control of type I IFN production. Although uptake and endosomal trafficking of TLR ligands were not affected in the presence of PI3K inhibitors, there was a dramatic defect in the nuclear translocation of IFN regulatory factor (IRF) 7, whereas nuclear factor κB activation was preserved. Thus, PI3K selectively controls type I IFN production by regulating IRF-7 nuclear translocation in human pDCs and could serve as a novel target to inhibit pathogenic type I IFN in autoimmune diseases.